Current Topics on Mathematics and Computer Science Vol. 4 - Ferreira, M. A. M. (2021)
This book covers key areas of mathematics and computer science. The contributions by the authors include intuitionistic fuzzy set, selecting specialization, distributed generation, inverter, photovoltaic, microgrid, one-dimensional parabolic partial differential equation, Spectral method, Legendre Pseudo–spectral method, Legendre Differentiation matrices, Kronecker product, computer science, programming, academic performance, examination, technology, institutional quality, Foreign direct investment, authentication code, multiuser authentication, message, verifiable secret sharing, key management, threshold., Scarification, Quantum mechanics, Kadison-Singer problem, state funded enterprises, economic performance, fuzzy sets, fuzzy entropy, Atanassov’s intuitionistic fuzzy entropy, exponential entropy, email and websites phishing, phishing detection techniques, user awareness on email phishing, distributed network, hybrid distributed systems, dynamic provisioning, metric space, contractive conditions, asymptotic formula, beta operators, linear positive operators, simultaneous approximation, unbounded functions, uniform continuity, adaptive collaborative system, dynamic environment, participant, problem solving, information sharing, ontology, knowledge-based systems, collaborative, adaptive and modelling, semantic web. This book contains various materials suitable for students, researchers and academicians in the field of mathematics and computer science.